PERANCANGAN SISTEM INFORMASI SIMPAN PINJAM DAN PENENTUAN SISA HASIL USAHA DI KOPERASI KOPPU P3J BANDUNG - Ardi Taryanto; Yudi Mardian (INFOKOM (Informatika & Komputer), 2023)
This study aimed to design and implement a savings, loans and surplus information system at Koperasi KOPPU P3J Bandung. This Koperasi is a business entity engaged in the field of cooperative economics, who serve members in particular in the field of savings and loans services. The data collection tecniques used were by interviews, observations and completed by literature study which had related with the problems. Software development methods was made using waterfall. From the research done, the factor that inhibited the saving and loans information system was still using the manual method and it was less effective and efficient. Therefore, in this research was made design saving and loans information system using Unified Modelling Languange (UML) and implemented by programming languages Microsoft Visual Studio 2010 and also the Microsoft Access as a DBMS (Database Management System). With the existence of this application as a means of processing of items saving and loans data processing then it was expected that data processing can run fast and in an optimum order